2008
DOI: 10.1002/chem.200800455
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Cross‐Coupling Reaction of α‐Metallated Alkenyl Sulfoximines and Alkenyl Sulfoximines with Cuprates Featuring a 1,2‐Metal‐Ate Rearrangement of Sulfoximine‐Substituted Higher Order Alkenyl Cuprates and an α‐Metallation of Alkenyl Sulfoximines by Cuprates

Abstract: (E)- and (Z)-configured alpha-lithioalkenyl sulfoximines, which are available through lithiation of the corresponding alkenyl sulfoximines, undergo a anionic cross-coupling reaction (ACCR) with organocuprates with formation of the corresponding alkenyl cuprates and sulfinamide. The alkenyl cuprates can be trapped by electrophiles. The ACCR presumably proceeds via the formation of a higher-order sulfoximine-substituted alkenyl cuprate, which undergoes a 1,2-metal-ate rearrangement whereby the sulfoximine group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…A pre-complex between the cuprate base and the sulfoximine group was proposed as a possible explanation for the reaction. 55 However, with the exception of this study, other examples reported in the literature concerning deprotometallation using cuprate bases have involved aromatic substrates. Moreover, it is noteworthy that these studies have focused on Lipshutz cuprates and, as defined in section 2 of this review, Lipshutz-type cuprates.…”
Section: Gilman Cuprates and Structural Interconversionmentioning
confidence: 68%
“…A pre-complex between the cuprate base and the sulfoximine group was proposed as a possible explanation for the reaction. 55 However, with the exception of this study, other examples reported in the literature concerning deprotometallation using cuprate bases have involved aromatic substrates. Moreover, it is noteworthy that these studies have focused on Lipshutz cuprates and, as defined in section 2 of this review, Lipshutz-type cuprates.…”
Section: Gilman Cuprates and Structural Interconversionmentioning
confidence: 68%
“…We had previously studied the RCDEM of trienes of type XIV (R 1 = alkenyl, Scheme ), which gave the corresponding medium‐sized carbocycles 14b. Alkenylsulfoximines XV are readily lithiated at the α‐position at low temperatures, with formation of the corresponding Z ‐configured α‐lithioalkenylsulfoximines 12e,12g,15b. At 0 °C they undergo isomerization to the corresponding E ‐configured α‐lithioalkenylsulfoximines, which can be trapped by unsaturated aldehydes to give the allylic alcohols XIV (R 1 = alkenyl) 14b.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, it stabilizes the electron‐rich metal center in the Ni 0 ‐intermediates and on the other hand it participates in controlling the reaction barriers that lead to the key Ni 0 ‐vinylidene and dianionic Ni 0 ‐ate intermediates of the ACCR pathways. The mechanism of the Ni catalyzed ACCR of lithioalkenyl sulfoximines is distinctly different from that of the Cu catalyzed ACCR of lithioalkenyl ethers and Cu mediated ACCR of litthioalkenyl sulfoximines, which has been postulated as key step a 1,2‐metalate shift of higher‐order cuprates under displacement of the nucleofuge at the sp 2 C atom.…”
Section: Discussionmentioning
confidence: 99%